Complexation between antimony and o-chlorophenylfluorone and its application to determination of antimony in wastewater - Pan, Lu-Ting (Array, 2009)
Summary: The formation of a chelate complex of antimony(III) with o-chlorophenylfluorone (CPF) was used for the spectrophotometric determination of antimony. The spectral correction technique was applied to characterize the complexation and the determination of SbIII. Results have shown that complex Sb(CPF)2H2O was formed and its stepwise stability constants were determined to be logK1 = 6.44 and logK2 = 5.81. The molar absorptivities of the complex at pH = 4.5 and at 540 nm were ε1 = 1.38×104 and ε2 = 3.46×104 dm3 mol–1 cm–1. The method is characterised by selectivity in the presence of the mixture of thiourea, triethanolamine and ethylenebis(oxyethylenenitrilo)-tetraacetic acid. The limit of detection is 0.03 µg cm–3 of SbIII. Analysis of wastewater samples was performed with satisfactory results